Effectiveness of cognitive restructuring and social decision-making techniques on truancy behaviour reduction among secondary school adolescents in Ibadan, Nigeria (2014)
This study investigated effectiveness of cognitive restructuring and social decision-making techniques on truancy reduction among secondary school adolescents m Ibadan, Nigeria. Pre-test, post-test, control group quasi-experimental design with a 3x2x2 factorial matrix was adopted for the study. A total of 180 Senior Secondary School adolescents was randomly selected from three purposively selected secondary schools, from 11 local government areas in Ibadan, using the multistage sampling procedure They were stratified proportionately into two experimental conditions - Cognitive Restructuring Technique (CRT) and Social Decision-Making Technique (SDMT) - and the control group. Two instruments, Truancy Behaviour Rating Scale (a = 0.78) and Student Motivation Scale (a = 0.77) were employed in the study. Three hypotheses were tested for significance at 0.05 alpha level. The data were subjected to Analysis of Covariance and Scheffe for post hoc analysis. There was a significant difference in the truancy reduction of the experimental participants and control group (Fp-nv = 51.40; P<0.05). The experimental participants (x=109.6. x = 103.5) performed better than the control (x = 126.134) on truancy behaviour reduction. Similarly, truancy declined among the participants treated with SDMT (x = 103.49) more than among those treated with CRT (x = 109.57) There was reduction in the truancy behaviour of high- and low- motivated participants (F/2.174) = 59.33; P< 20.05) Cognitive Restructuring and Social Decision-Making techniques were effective in the reduction of truancy among secondary school adolescents. Counselling and educational psychologists could make use of the two approaches to reduce the incidence of truancy in school.